Correction: Conjugated polymer-based luminescent probes for ratiometric detection of biomolecules. Issue 28 (6th July 2022) - Zhao, Lingfeng; Zhao, Can; Zhou, Jiasheng; Ji, Haiwei; Qin, Yuling; Li, Guo; Wu, Li; Zhou, Xiaobo
Abstract : Correction for 'Conjugated polymer-based luminescent probes for ratiometric detection of biomolecules' by Lingfeng Zhao et al., J. Mater. Chem. B, 2022, ; https://doi.org/10.1039/d2tb00937d .